2019
DOI: 10.1590/1678-4685-gmb-2018-0043
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenesis imperfecta in Brazilian patients

Abstract: Osteogenesis Imperfecta (OI) is a heterogeneous genetic disorder characterized by bone fragility and fracture. Mutations in 20 distinct genes can cause OI, and therefore, the genetic diagnosis of OI is frequently difficult to obtain because of the great number of genes that can be related with this disease. Studies that report the most frequently mutated genes in OI patients can help to improve molecular strategies for diagnosis of the disease. In order to characterize the mutation profile of OI in Brazilian p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…FKBP10 has eight domains including four FKBP domains, two EF-hands, one signal peptide and one ER locating domains. Several previous studies found that FKBP10 mutations disrupting the amino acid sequence of FKBP-type3 PPIase domain were a cause of recessive osteogenesis imperfecta and Bruck syndrome [ 26 , 27 ], which suggested that FKBP-type3 PPIase domain may paly a key role in the biological function of FKBP10. In the present study, we identified for the first time that FKBP10 interacts Hsp47 by FKBP-type3 PPIase domain in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…FKBP10 has eight domains including four FKBP domains, two EF-hands, one signal peptide and one ER locating domains. Several previous studies found that FKBP10 mutations disrupting the amino acid sequence of FKBP-type3 PPIase domain were a cause of recessive osteogenesis imperfecta and Bruck syndrome [ 26 , 27 ], which suggested that FKBP-type3 PPIase domain may paly a key role in the biological function of FKBP10. In the present study, we identified for the first time that FKBP10 interacts Hsp47 by FKBP-type3 PPIase domain in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The most common P3H1 allele causing OI is c.1080+1G>T, a founder mutation originating in West Africa that has been reported in patients of African-American ancestry (Cabral et al, 2012). Two Brazilian cases had been reported with this mutation by two independent groups (Barbirato et al, 2015;Trancozo et al, 2019). Scollo et al (2018) reported on a type VIII OI with P3H1 homozygous c.1914+1G>A and bilateral giant retina tears.…”
mentioning
confidence: 99%
“…In this study, we were able to obtain blood cells from one type I OI patient and confirmed that a T nucleotide was deleted (c.2523delT) from exon 36 of the COL1A1 gene, replacing the 842nd amino acid (glycine) with alanine and causing a frameshift mutation affecting 266 downstream amino acids. While this mutation is already reported in previous studies [ 43 ], the OI patient participating in this study exhibited OI-specific symptoms, such as bone fragility, frequent fractures, and bone deformations, as well as clinical symptoms, such as blue sclera. The expression of type I collagen was altered in the OI patient-derived cells; however, the results differed by the antibodies that were used.…”
Section: Discussionmentioning
confidence: 52%
“…MSCs generated from the gene-corrected iPSCs successfully differentiated into osteoblasts. Kawai et al attempted substituting the mutated nucleotides in OI-iPSCs with wild-type nucleotides by genome editing [ 43 ]. The abnormal features that showed during osteogenic differentiation in OI-iPSCs was successfully recovered.…”
Section: Discussionmentioning
confidence: 99%